2005
DOI: 10.1161/circulationaha.105.543686
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging After Stage I Norwood Operation for Hypoplastic Left Heart Syndrome

Abstract: Background-After the Norwood operation, a patient's suitability for proceeding to a bidirectional cavopulmonary connection (BCPC) is assessed by a combination of echocardiography and diagnostic cardiac catheterization. In this study, we describe the results of 37 patients who underwent cardiovascular magnetic resonance (MR) assessment before BCPC. Methods and Results-Cardiovascular MR and echocardiography were performed in 37 infants with hypoplastic left heart syndrome before BCPC, and the findings were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Gadolinium-enhanced MR angiography was performed as previously described11 with a coronal 3D fast-field-echo sequence. Gadolinium (Dotarem, Guerbet) was injected into a peripheral vein and tracked into the heart with a dynamic coronal 2D fast-field-echo sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Gadolinium-enhanced MR angiography was performed as previously described11 with a coronal 3D fast-field-echo sequence. Gadolinium (Dotarem, Guerbet) was injected into a peripheral vein and tracked into the heart with a dynamic coronal 2D fast-field-echo sequence.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16] Therefore, this noninvasive imaging modality can potentially provide an alternative to prebidirectional Glenn catheterization; indeed 1 retrospective cohort study demonstrated the feasibility of this approach. 17 The goal of this prospective, randomized, single-center trial of CMR versus catheterization in infants presenting for bidirectional Glenn operation was to test the hypothesis that CMR can provide the necessary anatomic and functional information required to evaluate such patients safely with fewer adverse events, reduced costs, and equivalent short-term postoperative outcomes.…”
Section: Clinical Perspective P 2725mentioning
confidence: 99%
“…Although not evaluated in this study, other studies have shown that cardiac MRI accurately and adequately visualizes anatomic details including mediastinal vessels such as the aortic arch, branch pulmonary arteries, and large systemic-to-pulmonary collateral vessels in patients with congenital heart disease [1013, 22, 27, 29]. Its preoperative use could, therefore, show additional anatomic abnormalities missed by echocardiography and significantly reduce the need for anatomic assessment by catheterization.…”
Section: Discussionmentioning
confidence: 87%